2014
DOI: 10.4236/ojmp.2014.31012
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Life Skills Training on Enhancing the Self-Esteem of Hearing Impaired Students in Inclusive Schools

Abstract: This research investigates the effectiveness of life skills training on enhancing the self-esteem of 8-16 years-old students with hearing impairment in inclusive schools. The sample was included of 54 students with hearing impairment from inclusive school whom their age and IQ were matched. They were randomly divided into an experimental and a control group (27 students in each group). The participants were assessed by Coopersmith Self-esteem Inventory (58-items version). The gathered data were analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…This finding is similar to that of the study by Mahvashevernosfaderani, Adibsereshki, and Movallali [41], which concluded that life skills training has significant effect on the cooperation, assertion, and self-control skills in the hearing loss students. Furthermore, these results are similar to that of the study by Kazemi, Momeni, and Kiamarsi [37], which concluded that training of life skills increases behavioral skills of students with dyscalculia.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is similar to that of the study by Mahvashevernosfaderani, Adibsereshki, and Movallali [41], which concluded that life skills training has significant effect on the cooperation, assertion, and self-control skills in the hearing loss students. Furthermore, these results are similar to that of the study by Kazemi, Momeni, and Kiamarsi [37], which concluded that training of life skills increases behavioral skills of students with dyscalculia.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were reported in the studies conducted Parvathy and Renjith R Pillai (2015) and Pujar et al, (2014). A study conducted by Vernosfaderani (2014) revealed that there was enhancement of self-esteem after implementation of Life skills training programme this study also found that in the experimental group the mean pretest score in Self-esteem was 16.9 and the post test score was 20.1 and in the control group the pretest score was 13.7 and the post test score was 14.8.…”
Section: Group-wise Comparisonmentioning
confidence: 62%
“…For explanation this result can concluded that although some deaf students are able to pick up positive skills through their everyday interactions with adults and peers, it is important that educators and parents reinforce learning of social skills with direct and indirect training of life skills [19][20][21][22][23]. As a result of this increase in change scores within the experimental group, it can be assumed that over time a life skills training curriculum can have positive effects.…”
Section: Discussionmentioning
confidence: 97%